A World without Capitalism? Alternative Discourses, Spaces, and Imaginaries - Chun, Christian W. (Taylor & Francis, 2022)
In this book, Christian W. Chun examines the ways in which identities, discourses, and topographies of both capitalist and anti-capitalist imaginaries and realities are embodied in the everyday practices of people. A World without Capitalism? is a sociolinguistic ethnography that explores the heretofore limited research in applied linguistics and sociolinguistics on the discursive and materialized representations and enactments of capitalism. Engaging across disciplinary fields, including applied linguistics, ethnography, political economy, philosophy, and cultural studies, Chun investigates in ethnographic detail how capitalism does and does not pervade people's everyday experiences. This book aims to further contribute to a much-needed understanding of how discourses operate in the co-constructions of capitalist and anti-capitalist imaginaries and instantiated realities and practices as narrated, lived, and embodied by people and material artifacts. This book is vital reading for students and researchers working in the fields of applied linguistics, discourse analysis, and cultural studies, as well as those interested in understanding capitalism and questioning how to live beyond it.